The Quality Of Curly Red Chili Seeds (Capsicum Annum L) From Fresh Fruit Is Affected By The Concentration Of Salt Water Solution - Nasution, Tri Susanti Rahmadhani; Dian Priskilla Mendrofa; Mendrofa, Ayu Indah Purnama; Tritumeiman Waruwu; Irwan Saham Laia; Rahmad Winanda Telaumbanua; Natalia Kristiani Lase (Jurnal Agroekoteknologi Terapan, 2025)
This study aims to assess the effect of salt solution concentration on the quality of curly red chili (Capsicum annuum L.) seeds produced from fresh fruit. The method used was a laboratory experiment with five salt solution concentrations (0.5%, 1%, 1.5%, 2%, and 2.5%). Parameters observed included germination, seed vigor, and initial plant dry weight. Selection was done by soaking the seeds in salt solution for 6-8 hours to separate high-quality seeds (sinking) from unfit seeds (floating). The results showed that the concentration of salt solution significantly affected seed quality. The optimal concentration was in the range of 1%-1.5%, which resulted in the highest germination (92%), best vigor, and maximum initial plant dry weight (0.25 grams). In contrast, concentrations above 2% caused a decline in seed quality due to osmotic stress, inhibiting water and nutrient absorption. This study concludes that the salt solution-based selection method effectively improves the quality of curly red chili seeds with an optimal concentration of 1%-1.5%. This method is simple, economical, and can be applied to support sustainable agricultural practices, especially in horticultural seed production. Keywords: Seed; Salt Solution; Curly Red Chili; Germination; Vigor Abstrak Penelitian ini bertujuan untuk mengkaji pengaruh konsentrasi larutan garam terhadap mutu benih cabai merah keriting (Capsicum annuum L.) yang dihasilkan dari buah segar. Metode yang digunakan adalah eksperimen laboratorium dengan perlakuan lima konsentrasi larutan garam (0,5%, 1%, 1,5%, 2%, dan 2,5%). Parameter yang diamati meliputi daya kecambah, vigor benih, dan berat kering tanaman awal. Seleksi dilakukan dengan merendam benih dalam larutan garam selama 6–8 jam untuk memisahkan benih berkualitas tinggi (tenggelam) dari benih yang tidak layak (terapung). Hasil penelitian menunjukkan bahwa konsentrasi larutan garam secara signifikan memengaruhi mutu benih. Konsentrasi optimal berada pada rentang 1%-1,5%, yang menghasilkan daya kecambah tertinggi (92%), vigor terbaik, dan berat kering tanaman awal maksimal (0,25 gram). Sebaliknya, konsentrasi di atas 2% menyebabkan penurunan kualitas benih akibat stres osmotik, yang menghambat penyerapan air dan nutrisi. Kesimpulan dari penelitian ini adalah metode seleksi berbasis larutan garam efektif dalam meningkatkan mutu benih cabai merah keriting dengan konsentrasi optimal 1%-1,5%. Metode ini sederhana, ekonomis, dan dapat diterapkan untuk mendukung praktik pertanian berkelanjutan, khususnya dalam produksi benih hortikultura. Kata Kunci: Benih; Larutan Garam; Cabai Merah Keriting; Daya Kecambah; Vigor